2006
DOI: 10.2165/00019053-200624120-00005
|View full text |Cite
|
Sign up to set email alerts
|

Generic Health-Related Quality-of-Life Assessment in Children and Adolescents

Abstract: The health-related quality of life (HR-QOL) of children and adolescents is increasingly considered a relevant topic for research. Instruments to assess quality of life in children and adolescents of a generic as well as disease- or condition-specific nature are being developed and applied in epidemiological surveys, clinical studies, quality assurance and health economics. This paper attempts to give an overview on the state of the art of HR-QOL assessment in children as it relates to methodological and concep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
355
1
14

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 358 publications
(378 citation statements)
references
References 92 publications
8
355
1
14
Order By: Relevance
“…A disadvantage of adopting generic measures is that they may be less sensitive or responsive to small but relevant changes related to disease status. 27 Finally, although this study was based on a sample-size calculation as well as on a high response rate, the subjects were not randomly selected. Thus, participants are not fully representative of the overall population, and conclusions should be interpreted with caution.…”
Section: 13mentioning
confidence: 99%
“…A disadvantage of adopting generic measures is that they may be less sensitive or responsive to small but relevant changes related to disease status. 27 Finally, although this study was based on a sample-size calculation as well as on a high response rate, the subjects were not randomly selected. Thus, participants are not fully representative of the overall population, and conclusions should be interpreted with caution.…”
Section: 13mentioning
confidence: 99%
“…Research in this area focuses rather on children's and adolescents' own somatic or psychiatric illness (Ravens-Sieberer & Bullinger, 1998;Ravens-Sieberer et al 2006, 2008Mattejat et al 2005). Studies have shown that mentally ill children have a lower health-related quality of life (HRQL) than healthy or somatically ill children (Mattejat & Remschmidt, 2003;RavensSieberer et al, 2008).…”
Section: Quality Of Life In Children Of Mentally Ill Parentsmentioning
confidence: 99%
“…21 To measure child mental health, we used standardized scales that assessed both externalizing problems (attention problems, oppositional behavior, and conduct problems) and internalizing problems (mood and anxiety). Overall mood was measured with the KIDSCREEN 7-item child report General Mood subscale 26,27 ; depression was measured using the Children's Depression Inventory (CDI) 10-item short form; anxiety was measured using the Multidimensional Anxiety Scale for Children 10 instrument 28 ; and measures of inattention, conduct, and cooperativeness were taken from the Statistics Canada National Longitudinal Study of Children and Youth, Canadian population health survey. 29 Parental support was measured using the KIDSCREEN 6-item child report Home subscale.…”
mentioning
confidence: 99%
“…29 Parental support was measured using the KIDSCREEN 6-item child report Home subscale. 26,27 General peer support was measured using the Classmate subscale of the Harter 30 Social Support Scale for Children, child and adolescent versions. All child self-report measures were scored positively such that a higher score represented more of the desirable trait.…”
mentioning
confidence: 99%